ANALISIS STATISTICAL QUALITY CONTROL PADA PENGENDALIAN KUALITAS PRODUK KULINER - Supardi Supardi; Agus Dharmanto (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
The BFC brand geprek chicken in Bekasi City still suffered 1.77% damage. The aims of this study are to determine the quality control of BFC Brand Geprek Chicken. The data analysis is used Statistical Quality Control method with histogram, control chart, fishbone diagram. Using secondary data on July-September 2020 periods. The results showed that there were three types of damage namely burnt geprek chicken, geprek chicken flour was not crispy and geprek chicken was not yet cooked. The damage that occurs is still within the control limit value, the cause of the first damage from the human factor is the staff doing the frying while serving, the machine factor, if the stove control is turned to low it will die, from the method factor is frying simultaneously for all sizes. The second damage, the cause of the human factor is that it still uses an approximate model in making the dough, the method factor is taking the flour directly from the flour sack, the cause of the third damage of human factors is only seeing the flour that has changed and from the machine factors is unable to turn the fire control to a low position on the stove.